SEMANTIC STRUCTURE OF PHRASEOLOGICAL UNITS IN THE UZBEKISTAN LANGUAGE AND THEIR PLACE IN THE NATIONAL MENTALITY - Zokirova Sevara (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
This article provides an in-depth analysis of the semantic structure of phraseological units in the Uzbek language and their place in the national mentality. The classification of phraseological units, semantic features (polysemy, synonymy, variation, antonymy and homonymy) and the reflection of national culture through somatic components are considered in detail. The study highlights the current issues of Uzbek linguistics, presents phraseologisms as a means of national identification, and also analyzes professional phraseologisms and cultural images through examples. The results reveal the cognitive and cultural layers of the language and serve as a basis for modern linguistic research, which emphasizes the anthropocentric paradigm of Uzbek phraseology.